Report of The Committee on Pre-School Children Feeding Programmes - Planning Commission (Planning Commission, 1972)
A suggestion was made in a meeting of the Nutrition Coordination Group presided by Member .(Agriculture), Shri B. Venkatappiah on 28th October, 1970 to constitute a Committee on Pre-School Feeding Programmes. The Coordination Group had considered various aspects of nutrition feeding programmes. It was proposed that an integrated picture of all feeding programmes catering to pre-school children should be obtained. Accordingly, the Planning Commission constituted the Committee on Pre-School Children Feeding Programmes. A copy of the office memorandum constituting the Committee is at Annexure 1. Consequent upon internal changes in subjects allotted to Joint Secretaries of Department of Food, Shri G.C.N. Chahal took the place of Shri R. Balasubramanian.
Government of India Planning Commission
Government of India Planning Commission